Total femur resection and endoprosthesis reconstruction utilizing the dual incision surgical approach in patients with femur bone sarcoma: A case series - Ahmad Shehadeh; Muhamad A. Al-Qawasmi; Muntaser Abu Shokor (Journal of Orthopaedic Reports)
Preserving limb function following the excision of tumors involving the entire femur poses a significant therapeutic challenge. Bone sarcomas affecting nearly the entire femur often require radical excision, entailing the removal of the entire femur bone and extensive resection of muscles involved in hip and knee function. Traditionally, the surgical approach to large femoral tumors necessitated amputation via hip disarticulation. However, emerging techniques such as Total Femur Replacement (TFR) offer the possibility of limb preservation. Compared to amputation, limb-sparing surgery is more cost-effective and better tolerated by patients. Over the long term, it is associated with lower oxygen consumption and energy requirements per meter walked. In this case series we present a comparison between the standard single incision approach and the dual incision approach for TFR. Level of evidence: Case series, Level IV.